Role of Oral Medium Chain Triglyceride Oil in Low Birth Weight Neonates: A Randomized Controlled Trial - Hameed, Rida; Asif, Aqsa Arooj (Indus Journal of Bioscience Research, 2025)
Introduction: Low birth weight neonates are at increased risk of poor neurodevelopmental outcomes. Head circumference is an important anthropometric measure that correlates with brain growth and neurodevelopment. Medium chain triglycerides (MCT) oil provides readily available energy and may support growth in preterm and low birth weight infants. Methodology: This randomized controlled trial was conducted at the Department of Pediatrics, Sharif Medical City Hospital, Lahore, from August 7, 2024 to February 6, 2025. A total of 460 low birth weight neonates (birth weight